Towards a 'bright future': young people overcoming poverty and risk in two Ethiopian communities - Chuta, N; Crivello, G (Young Lives, 2013)
This paper explores young people’s views and experiences of poverty and everyday risks in two contrasting communities in Ethiopia. The data are from Young Lives, a long-term study of childhood poverty. Qualitative data were collected with a group of children born in 1994, at three time points (when they were aged 12, 13 and 16). The paper develops three lines of argument with respect to the multiple risks that young people negotiate as they transition to adulthood. The first point has to do with the role of local environments in shaping the risks that young people face, such that young men and women experience their spatial environments differently, and some risks differ by location (rural/urban). The second has to do with the way poverty exacerbates other risks in the transition to adulthood, by limiting choices and horizons, and by creating a sense of uncertainty. The third point has to do with the importance of social risks for young people, and the way that risks become more gender-differentiated and sexualised, in both the rural and urban settings, as children get older. This study finds that young people attempt to manage their material needs and livelihood strategies alongside their moral concerns to secure ‘bright futures’ for themselves and to become the kind of men and women who are looked up to in their societies. Policies and programmes wishing to support young people in poverty need also to be sensitive to the social and moral dimensions of their experiences.